Treatment of Increased Intracranial Pressure and Vasospasm after Subarachnoid Hemorrhage in a 9-Year-Old Child—A Case Report - Müller, Sarah-Hélène; Taschner, Christian; Meckel, Stephan; Mayerhofer, Ernst; Roelz, Roland; Bansbach, Joachim (Journal of Pediatric Neurology, 2021)
In this article, we reported a 9-year-old male child patient who suffered severe subarachnoid hemorrhage due to ruptured dissecting aneurysm of the left parieto-occipital artery. After endovascular occlusion of the aneurysm, increased intracranial pressure refractory to noninvasive therapy required secondary decompressive hemicraniectomy. Critical vasospasm and delayed neurological deterioration were treated by oral nimodipine and successful endovascular rescue therapy consisting of intra-arterial balloon dilatation.
Keywords: pediatric; intracranial; aneurysm; vasospasm